Verification of Immune Debts in Children Caused by the COVID-19 Pandemic from an Epidemiological and Clinical Perspective - Masayuki Nagasawa (Immuno)
Social behavior restrictions, social distancing, and promotion of non-pharmaceutical interventions (NPIs) during the COVID-19 pandemic have significantly reduced the incidence of many epidemic infections in the world, especially in children. Resurges of infectious diseases vary depending on the biological characteristics of each infectious pathogen and differences in culture, lifestyle, and infection control mitigation policies by country or region. Although the gapping of infectious disease outbreaks can cause children who were uninfected during that period to become more susceptible to infection after the pandemic, resulting in a slightly older age of infected children, there are no conclusive reports that suggest a definite impact on the development of children’s immune maturation or its balance. Insufficient immune challenges in early life may influence the risk of developing immune-mediated conditions such as allergies or autoimmune diseases later in life, though evidence for this is still emerging. Future observational studies are needed to determine the long-term impact of the epidemic gap caused by the COVID-19 pandemic as well as the long-term impact of COVID-19 infection itself on the immune function or balance of children.